2022
DOI: 10.1093/ofid/ofac365
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Integrating Behavioral Health Services Into HIV Clinical Care: A Narrative Review

Abstract: The integration of behavioral health services within HIV care settings holds promise for improving substance use, mental health, and HIV-related health outcomes for people with HIV. As part of an initiative funded by the Health Resources and Services Administration’s HIV/AIDS Bureau, we conducted a narrative review of interventions focused on behavioral health integration in HIV care in the U.S. Our literature search yielded 19 intervention studies published between 2010 and 2021. We categorized the interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Minority stress from racial and anti-trans stigma on top of HIV stigma may exacerbate psychological distress while also reducing help-seeking for mental health support [ 34 ]. From a systems perspective, a key component to ensure success of integrated and culturally tailored substance use and mental health treatment is screening and referral [ 35 ]. We found that referrals for trans women with indicators of mental distress were low, suggesting that screening protocols may not be in place for behavioral health needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minority stress from racial and anti-trans stigma on top of HIV stigma may exacerbate psychological distress while also reducing help-seeking for mental health support [ 34 ]. From a systems perspective, a key component to ensure success of integrated and culturally tailored substance use and mental health treatment is screening and referral [ 35 ]. We found that referrals for trans women with indicators of mental distress were low, suggesting that screening protocols may not be in place for behavioral health needs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, we did identify a need for interventions to improve behavioral health engagement among trans women living with HIV with a focus on mitigating health inequities within the population. Integration of outpatient substance use services and low threshold mental health services into HIV care may improve engagement [ 35 , 49 ]. Promising examples are emerging from the integration of opioid agonist treatment (OAT) services that are embedded within HIV care.…”
Section: Discussionmentioning
confidence: 99%
“…The first step toward integration of mental health and OUD treatment in HIV care is effective, universal screening of these conditions at every HIV care appointment [ 25 ]. However, several barriers to screening and integration have been identified, including lack of provider awareness and time and resource constraints [ 28 , 29 ]. A systematic review identified six studies examining the integration of treatment for OUD in HIV care settings, five of which focused on MAT and one of which offered counseling only [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first step toward integration of mental health and OUD treatment in HIV care is effective, universal screening of these conditions at every HIV care appointment [25]. However, several barriers to screening and integration have been identified, including lack of provider awareness and time and resource constraints [28,29]. A systematic review identified six studies examining the integration of treatment for OUD in HIV care settings, five of which focused on MAT and one of which offered counseling only [27].…”
Section: Introductionmentioning
confidence: 99%